2014
DOI: 10.1590/0104-1169.3415.2414
|View full text |Cite
|
Sign up to set email alerts
|

Maternal Eating and Physical Activity Strategies and their Relation with Children's Nutritional Status

Abstract: Objectives to describe the maternal eating and physical activity strategies (monitoring, discipline, control, limits and reinforcement) [MEES]; to determine the relation between MEES and the child's nutritional status [body mass index (BMI) and body fat percentage (BFP)]; to verify whether the MEES differ according to the child's nutritional status. Method participants were 558 mothers and children (3 to 11 years of age) who studied at public schools. The Parental Strategies for Eating and Activity Scale (PEAS… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
15
0
2

Year Published

2015
2015
2022
2022

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(17 citation statements)
references
References 21 publications
0
15
0
2
Order By: Relevance
“…The remaining 19 articles were reviewed in their entirety, and 9 of them were excluded for not meeting the study selection criteria: studied populations did not live in Latin America or the Caribbean [ 13 , 24 , 25 , 26 ]; in addition to not being conducted in LAC, one of these studies used a qualitative method [ 25 ]; weight status was not included as an outcome variable [ 27 , 28 , 29 , 30 ], and one of them also studied children who were out of the age range of 2 to 12 years old [ 31 ]. The remaining 10 articles [ 32 , 33 , 34 , 35 , 36 , 37 , 38 , 39 , 40 , 41 ] were included in the review.…”
Section: Resultsmentioning
confidence: 99%
“…The remaining 19 articles were reviewed in their entirety, and 9 of them were excluded for not meeting the study selection criteria: studied populations did not live in Latin America or the Caribbean [ 13 , 24 , 25 , 26 ]; in addition to not being conducted in LAC, one of these studies used a qualitative method [ 25 ]; weight status was not included as an outcome variable [ 27 , 28 , 29 , 30 ], and one of them also studied children who were out of the age range of 2 to 12 years old [ 31 ]. The remaining 10 articles [ 32 , 33 , 34 , 35 , 36 , 37 , 38 , 39 , 40 , 41 ] were included in the review.…”
Section: Resultsmentioning
confidence: 99%
“…19 Los niños sin exceso de peso tuvieron mayor exposición a altos grados de control parental, lo que es opuesto a otros reportes. 8,14,[20][21][22] En otros estudios se observó que los niños con alto nivel de control de sus patrones de alimentación y actividad física aumentan algunos indicadores del estatus corporal (IMC, porcentaje de grasa) o conductual (comer sin apetito). Basado en una prueba de c 2 de igualdad de proporciones *Punto de corte: para cada subescala se tomaron las puntuaciones superiores a 1 desviación estándar debajo del promedio.…”
Section: Discussionunclassified
“…Por lo anterior, es conveniente que las instituciones de salud incorporen la evaluación rutinaria de las prácticas parentales de alimentación y actividad física en sus programas de vigilancia y prevención de exceso de peso. Aunque aún es poco clara la direccionalidad de la asociación, con algunos estudios que reportan asociaciones positivas 12,14,20 y otros inversas, 11,[24][25][26] el control parental de las conductas alimentarias y de actividad física de los niños se relaciona con su tamaño corporal.…”
Section: Génerounclassified
“…In Mexico, a study on mothers and children residing in 5 northeastern states found that 68% of mothers of overweight children and 75% of mothers of obese children underestimated their preschoolers’ body weight [ 14 ]. In addition, Mexican and Hispanic mothers exert control and discipline that could lead to over consumption of foods and increased obesity risk [ 15 , 16 ]. More problematic, when mothers were not aware of their children’s overweight status, they had a lower self-efficacy to manage behaviors related to their child’s weight in comparison to mothers of normal weight children [ 17 , 18 ].…”
Section: Introductionmentioning
confidence: 99%